Radikalisme Gerakan Al-Ikhwan Al-Muslimun Mesir 1928–1948: Radicalism of the Muslim Brotherhood Movement in Egypt, 1928–1948 - Safruddin Edi Wibowo (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2006)
The Egyptian Muslim Brotherhood (Al-Ikhwan Al-Muslimun), founded in 1928 as a peaceful educational and da'wah movement, increasingly engaged in political violence and terrorism between 1928 and 1948. This study examines the socio-political, ideological, and educational roots of this radical shift. Using a historical method with chronological and thematic analyses of primary documents (Ikhwan's official publications) and secondary sources, the research finds that state repression, British imperialism, and political exclusion fueled the Brotherhood's turn to violence. Ideologically, the group’s belief in Islam’s holistic, indivisible nature led to an exclusionary worldview that delegitimized secular authorities and justified jihad as armed struggle. Education and indoctrination through the usrah (family) system and the secret apparatus (al-jihaz al-sirri) militarized members, promoting martyrdom and violent confrontation. The study concludes that radicalism was not inherent but emerged from specific political pressures and ideological absolutism, and recommends that non-violent cultural and educational approaches are more effective for Islamic reform than political violence. Gerakan Ikhwanul Muslimin Mesir yang didirikan pada 1928 sebagai gerakan pendidikan dan dakwah yang damai, justru semakin terlibat dalam kekerasan politik dan terorisme antara tahun 1928 hingga 1948. Penelitian ini mengkaji akar sosial-politik, ideologis, dan pendidikan dari pergeseran radikal tersebut. Dengan metode sejarah dan analisis kronologis-tematis terhadap dokumen primer dan sekunder, temuan menunjukkan bahwa represi negara, imperialisme Inggris, dan pengecualian politik mendorong Ikhwan pada kekerasan. Secara ideologis, keyakinan akan keutuhan Islam melahirkan pandangan eksklusif yang menolak otoritas sekuler dan membenarkan jihad sebagai perang bersenjata. Pendidikan dan indoktrinasi melalui sistem usrah dan aparat rahasia memiliterisasi anggota, mempromosikan mati syahid. Kesimpulannya, radikalisme Ikhwan bukan bawaan, tetapi muncul dari tekanan politik dan absolutisme ideologis. Rekomendasinya, pendekatan kultural dan pendidikan non-kekerasan lebih efektif untuk reformasi Islam.